Growth of Critically Endangered annual fish Austrolebias wolterstorffi (Cyprinodontiformes: Rivulidae) at different temperatures - Fonseca,Alinca Peres da (2013)
Given the importance of knowledge of the biology of endangered species for the planning of conservation and management efforts, the aim of this study was to investigate the influence of temperature on the growth of Austrolebias wolterstorffi (Ahl, 1924). To clarify the thermal influence on the growth of the species, temperatures of 16, 20, 24 , and 28°C were tested in triplicate. The present study showed that a water temperature of 28°C is detrimental to the growth of the species. Among the other tested temperatures, it was found that the optimum temperature for growth decreases as an individual ages and is slightly lower for females. It was demonstrated here that males reach a higher weight and length, and grow faster than females, reaching sexual maturity earlier. To optimize the growth of this species in captivity, the ideal temperature of the water during the initial life period is 24°C, until after puberty when the temperature should decrease to about 21°C.